PENGARUH KOMBINASI PUPUK KANDANG DAN NPK TERHADAP KADAR PROTEIN KASAR DAN SERAT KASAR RUMPUT ODOT (PENNISETUM PURPUREUM CV. MOTT) DEFOLIASI PERTAMA - Arifin, Nurul; Hidayat, Nur; Munasik, Munasik (ANGON: Journal of Animal Science and Technology, 2022)
Background. The research entitled "Effect of Combination of Manure and NPK on Crude Protein Content and Crude Fiber of Odot Grass (Pennisetum Purpureum Cv. Mott) First Defoliation" was carried out from 17 February to 10 May 2018 at Experimental Farm and Agrostology Laboratory, Faculty of Animal Science, Jenderal Soedirman University, Purwokerto. The research objective was to examine the effect of giving the optimum combination of manure and NPK levels in terms of crude protein content and crude fiber content of odot grass. Materials and methods. The material used in the study was the first defoliated of Odot grass plant which was initially planted on a total area of 278 m2 with an area of 5 m2 for each plot or unit and a spacing of 0.75 mx 0.35 m so that 720 stems of odot grass cuttings were needed, 270 kg of manure and 2.5 kg of NPK fertilizer. The method used was a factorial pattern experiment with a randomized block design. The first factor was manure consisting of K0: manure 0 kg / 5m2, K 1: manure 7.5 kg / 5m2, K2: manure 15 kg / 5m2 and the second factor is NPK fertilizer (M) which consists of M0 : NPK fertilizer 0 g / 5m2, M1: NPK fertilizer 37.5 g / 5m2, M2: NPK fertilizer 75 g / 5m2 and M3: NPK fertilizer 112.5 g / 5m2. The variables measured were crude protein content and crude fat content of the first defoliated Odot grass. Results. The results of the analysis of variance showed that the interaction between manure and NPK did not have a significant effect on crude protein content but had a very significant effect on crude fiber content. The higher the level of manure and NPK will increase the crude protein content and crude fiber of the first defoliated Odot grass.